2012
DOI: 10.1096/fj.12-209841
|View full text |Cite
|
Sign up to set email alerts
|

Bone structure and B‐cell populations, crippled by obesity, are partially rescued by brief daily exposure to low‐magnitude mechanical signals

Abstract: Deterioration of the immune and skeletal systems, each of which parallel obesity, reflects a fragile interrelationship between adiposity and osteoimmunology. Using a murine model of diet-induced obesity, this study investigated the ability of mechanical signals to protect the skeletal-immune systems at the tissue, cellular, and molecular level. A long-term (7 mo) high-fat diet increased total adiposity (+62%), accelerated age-related loss of trabecular bone (-61%), and markedly reduced B-cell number in the mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 59 publications
(88 reference statements)
9
62
0
Order By: Relevance
“…The mesenchymal stem cell (MSC) is a pluripotent progenitor that has the ability to differentiate into cells that form bone, fat, tendon, muscle and ligament. Accumulating evidence indicates that fate selection of marrow-based MSCs is influenced by mechanical signals, biasing differentiation of MSCs toward bone and away from fat (Luu et al, 2009a;Ozcivici et al, 2010;Chan et al, 2012;Pagnotti et al, 2012). It has further been shown that bone marrow in some skeletal elements may contain MSCs with greater osteogenic potential than those located in the marrow of other elements (Risbud et al, 2006;Volk et al, 2012), which would suggest that some bones may be more responsive to exerciseinduced mechanical signals than others.…”
Section: Introductionmentioning
confidence: 99%
“…The mesenchymal stem cell (MSC) is a pluripotent progenitor that has the ability to differentiate into cells that form bone, fat, tendon, muscle and ligament. Accumulating evidence indicates that fate selection of marrow-based MSCs is influenced by mechanical signals, biasing differentiation of MSCs toward bone and away from fat (Luu et al, 2009a;Ozcivici et al, 2010;Chan et al, 2012;Pagnotti et al, 2012). It has further been shown that bone marrow in some skeletal elements may contain MSCs with greater osteogenic potential than those located in the marrow of other elements (Risbud et al, 2006;Volk et al, 2012), which would suggest that some bones may be more responsive to exerciseinduced mechanical signals than others.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists considering OVX as a model to evaluate countermeasures for osteopenia must take into account the possibility that the rapid rate of bone loss may severely challenge the ability of any given therapy to restore the compromised architecture. Perhaps the outcome of this study would have been different with longer trials [19,28,29], earlier interventions [30,31], or refractory periods [32,33] to augment the responsiveness of the skeleton.…”
Section: Discussionmentioning
confidence: 98%
“…In that context, it is important to recognize that exercise in general and mechanical signals in particular, including the low impact signals engendered by low intensity vibrations (LIV), have been shown to be anabolic to the skeleton while simultaneously suppressing fat accumulation [18,17,19,16].…”
Section: Introductionmentioning
confidence: 99%
“…This inverse bone and fat relationship has been seen in models of osteoporosis 81 but is not so clear in obesity models. Nevertheless, high levels of MAT observed in the aged population, 82,83 obesity, 84 and postmenopausal women 80 have the potential to alter marrow homeostasis and crowd resident marrow cell populations, including immune and stem cells, and may have negative effects on hematopoiesis resulting from paracrine signaling. 81 This is an area of heavy research as we continue to learn more about the role of MAT in the pathogenesis of obesity.…”
Section: Impact Of Obesity On Musculoskeletal Tissue Systemsmentioning
confidence: 99%